2013
DOI: 10.1016/j.compenvurbsys.2012.08.008
|View full text |Cite
|
Sign up to set email alerts
|

3D cadastre in the Netherlands: Developments and international applicability

Abstract: a b s t r a c tThis paper presents the design and implementation of the cadastral system extension for registration of 3D rights and restrictions in the Netherlands fitting within the ISO 19152, Land Administration Domain Model (LADM) final draft international standard. The implementation will be conducted in two phases. The first phase of the solution does not require a change of the legal and cadastral frameworks and will be used to gain experience in the challenging domain of 3D cadastre where technical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 9 publications
(8 reference statements)
0
37
0
3
Order By: Relevance
“…See, for example, EL-Mekawy [5] and Atazadeh et al [18]. Furthermore, Stoter et al [14] have demonstrated the possibility to extract legal volumes from a BIM.…”
Section: Methodology For 3d Registrationmentioning
confidence: 99%
See 4 more Smart Citations
“…See, for example, EL-Mekawy [5] and Atazadeh et al [18]. Furthermore, Stoter et al [14] have demonstrated the possibility to extract legal volumes from a BIM.…”
Section: Methodology For 3d Registrationmentioning
confidence: 99%
“…Historical examples are cellars under the public street leading from canals to houses in the city of Utrecht. More recent examples are complex combinations of commercial areas, public transport hubs, and parking garages, or buildings over highways [14][15][16].…”
Section: Multi-level Property Rights In the Netherlandsmentioning
confidence: 99%
See 3 more Smart Citations